DEGREE OF SHORTNESS OF BREATH AND LOW IRON CONSUMPTION HABITS CAUSE DECREASED HEMOGLOBIN IN PATIENTS CONGESTIVE HEART FAILURE - Noor Eswanti; Alfiatur Rochma; Rusnoto Rusnoto; Muhamad Jauhar ((IJP) Indonesia Jurnal Perawat, 2024)
Congestive Heart Failure (CHF) causes the blood supply to the lungs to decrease, and blood does not enter the heart. This condition causes a buildup of fluid in the lungs, thereby reducing the exchange of oxygen and carbon dioxide. Heart failure patients who experience chronic iron deficiency can increase the prevalence of anemia. Analyzing the Relationship between the degree of shortness of breath and low iron diet habits with a decrease in hemoglobin levels in CHF patients. This type of correlational analytical research uses a cross-sectional approach with independent variables (Degree of Shortness of Breath and Low Iron Consumption Habits) and dependent variables (CHF Patients). This research was conducted in October 2023 at a private hospital. The total sample was 31 respondents using consecutive sampling techniques. The instruments used were observation sheets measuring RR and hemoglobin, iron consumption behavior questionnaires. Data analysis used Spearman Rho test. There is a significant relationship between the degree of shortness of breath (p=0,000; r=-0,861) and iron consumption habits (p=0,000; r=0,913) with hemoglobin levels in CHF patients. The degree of shortness of breath and low iron consumption cause anemia in CHF patients. The hospital can provide interventions to monitor the degree of shortness of breath, provide foods high in iron to increase hemoglobin in CHF patients, and consider aspects of the degree of shortness of breath.